Moses in the Aramaic Magic Bowls: Scribal Authority and Self-Identification - Bhayro, Siam (Jewish Thought, 2025)
In this contribution, I discuss the references to Moses in the Jewish Aramaic magic bowls, with a view to understanding how and why the Jewish scribes responsible for the bowls laid claim to the legacy of Moses. In order to properly contextualise this, I also consider examples of western groups laying claim to the legacy of Moses, namely the rabbis, the scribes, and the early church, as well as the roles assumed by the scribes within their communities. I then consider the significance of the Moses references in the magic bowls in relation to the crossing of the Red Sea, the wilderness wanderings, the wilderness rebellions, and the revelation at the burning bush. The significance of the rod of Moses is also considered, along with possible representations of it in bowl art.